Glutathione peroxidase mimics based on conformationally-restricted, peri-like, 4, 5-disubstituted fluorene dichalcogenides. Issue 48 (30th November 2021) - Jagdev, Kesar; Tanini, Damiano; Lownes, Jack W.; Figliola, Carlotta; Male, Louise; Capperucci, Antonella; Grainger, Richard S.
Abstract : The synthesis, structure and properties of 4, 5-(bay)-substituted fluorene dichalcogenides and their oxides are investigated towards a new class of GPx mimic. Abstract : Glutathione peroxidase (GPx) regulates cellular peroxide levels through glutathione oxidation. GPx-mimics based on 4, 5-disubstituted fluorene diselenides, their oxides, and ditellurides show catalytic activities consistent with conformational restriction about the dichalcogen bond.